DIVISION XII: COMMISSION 55: COMMUNICATING ASTRONOMY WITH THE PUBLIC. (13th August 2015) - Christensen, Lars Lindberg; Russo, Pedro; Robson, Ian; Arcand, Kimberly Kowal; Fienberg, Richard Tresch; Ödman-Govender, Carolina; Sekiguchi, Kazuhiro; Wheeler, Pete; Zhu, Jin
Abstract : A good fraction of the Commission 55 (C55) Organizing Committee met in Beijing in August at the XXVIII IAU General Assembly, where C55 organized Special Session 14 (SpS14) entitled "Communicating Astronomy with the Public for Scientists." During our C55 business meeting, and again during an impromptu gathering a few days later, we discussed changes in the IAU's organizational and programmatic structure and how these changes might affect C55. This report summarizes key points and offers some ideas about what we're calling "C55 v2.0." For background and reference, see the C55 website athttp://www.communicatingastronomy.org .